Pengaturan dan Implementasi Prinsip Netralitas Aparatur Sipil Negara di Indonesia - Sarnawa, Bagus (Jurnal Media Hukum, 2017)
The State Civil Apparatus has a very important role in the implementation of the tasks of government and nation-building. Therefore, the State Civil Apparatus is an apparatus free from political intervention. In other words, as stated in the legislation, the State Civil Apparatus must be neutral. The neutrality of the State Civil Apparatus is a prohibition for the State Civil Apparatus to become a member or manager of a political party, so that the Civil State Apparatus is free from the influence and intervention of political parties in the performance of their duties and obligations. The regulation of the neutrality of the new State Civil Apparatus began in the New Order period with the issuance of Law No. 8 of 1974, and so on in Law 43 of 1999 and Law No. 5 of 2014 on State Civil Apparatus and its implementing regulations. In practice, the implementation of neutrality of the State Civil Apparatus has many obstacles and constraints. At the time of enactment of Law No. 8 of 1974 and Law No. 43 of 1999, the principle of State Civil State’s neutrality of neutrality is often violated, this is due to the strong influence of political parties in bureaucratic relations in government agencies. Therefore, in the period of Law No. 5 of 2014, efforts are made to minimize and even eliminate the influence of political parties on the State Civil Apparatus, one way is to establish the State Civil Apparatus Commission.